1990
DOI: 10.1073/pnas.87.19.7541
|View full text |Cite
|
Sign up to set email alerts
|

Identification and preliminary characterization of protein-cysteine farnesyltransferase.

Abstract: Ras proteins must be isoprenylated at a conserved cysteine residue near the carboxyl terminus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 23 publications
(38 reference statements)
1
77
0
Order By: Relevance
“…A protein farnesyltransferase (PFT) has recently been purified and characterized from several mammalian tissues (30)(31)(32). The PFT transfers a farnesyl moiety from farnesyl pyrophosphate to an unmodified form of c-Ha-ras p21 and appears to recognize the Cys-Ali-Ali-Xaa motif (30).…”
Section: Discussionmentioning
confidence: 99%
“…A protein farnesyltransferase (PFT) has recently been purified and characterized from several mammalian tissues (30)(31)(32). The PFT transfers a farnesyl moiety from farnesyl pyrophosphate to an unmodified form of c-Ha-ras p21 and appears to recognize the Cys-Ali-Ali-Xaa motif (30).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins include ras in crude extracts of yeast cells [2,18]. The requirement of two proteins, nuclear lamins and the yeast a-mating factor, which end genes, DPRI/RAMI (referred to here as DPRI) and RAM2 for with a unique C-terminal sequence, CysAAX (A is an aliphatic the yeast FTase activity suggested that the enzyme consisted of amino acid and X is the C-terminal amino acid) [1][2][3][4]. This two subunits encoded by these genes.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian protein farnesyltransferase (PFT) 1 farnesylates the cysteine residue in carboxyl-terminal cysteine-aa aliphatic -aa aliphatic -aa x (CAAX) sequences, where aa x is methionine, glutamine, serine, threonine, or cysteine (13)(14)(15)(16). Protein geranylgeranyl transferase-I (PGGT-I) shows specificity for cysteine-aa aliphaticaa aliphatic -leucine sequences (13,(17)(18)(19)(20).…”
mentioning
confidence: 99%